A Diesel Engine Model Including Exhaust Flap, Intake Throttle, LP-EGR and VGT. Part I: System Modeling. Issue 15 (2015) - Reß, Johannes; Stürzebecher, Christoph; Bohn, Christian; Märzke, Frank; Frase, Robert
Abstract: A mean-value model of a diesel engine with variable geometry turbocharger, intake throttle, exhaust flap and low pressure exhaust gas recirculation throttle is developed in this paper. To simplify the model, the number of states is reduced to a minimum. Thus, the complete model has eleven states. The model consists of submodels which were optimized by polynomial functions. The optimization parameters are linear coefficients of the polynomial functions.